Disseminated histoplasmosis in a kidney transplant patient - Taksaon Angsutararux (2020)
© 2020 Wiley Periodicals LLC Patients with impaired cell-mediated immunity have a higher risk of developing histoplasmosis; however, histoplasmosis after solid organ transplantation is rare. In Thailand, histoplasmosis cases are sporadic, and most cases are associated with human immunodeficiency virus (HIV) infection. Herein, we report a case of disseminated histoplasmosis in a kidney transplant Thai recipient diagnosed by fungal staining of fungal culture from bronchoalveolar lavage and bone marrow biopsy. Liposomal amphotericin B was given followed by oral itraconazole. The patient's clinical condition was improved; however, his graft function was irreversibly declined. The majority of histoplasmosis cases after solid organ transplant presented with disseminated disease with pulmonary involvement. Even in a non-endemic area of histoplasmosis, suspected cases should be early diagnosed and promptly managed in order to reduce morbidity and mortality, especially in cell-mediated immunity defect patients like solid organ transplant recipients.